Pengaruh Media Tanam dan Waktu Panen Pada Pertumbuhan Serta Hasil Microgreen Peashoot (Pisum sativum L) : Urban farming, microgreen, peashoot, media tanam, umur panen - Ayyi, Benita Amirotul; Muslikah, Siti; Sugiarto; Zamarudah, Zuhanid (Universitas Islam Malang, 2025)
The reduction of agricultural land due to conversion for housing and rapid urbanization has led to the importance of urban farming in cities. Microgreen Peashoot (Pisum sativum L), which is rich in nutrients and beneficial for health. This study aimed to explore the effect of planting media and harvesting age on the growth and yield of microgreen Peashoot. The research was conducted at the Microgreen House, Alamsari Housing, Malang, using a Factorial Randomized Group Design (RAK) with two factors: planting media (100% cocopeat, 50% cocopeat: 50% husk charcoal, non-woven fabric) and harvest age (6, 7, 8, and 9 hst). The results showed that the combination of planting media cocopeat 50%: husk charcoal 50% harvest age at 9 hst to produce the best growth and yield. This combination is recommended for optimal microgreen peashoot yield.